Huge Neck Masses Causing Respiratory Distress in Neonates: Two Cases of Congenital Cervical Teratoma - Hasan Özkan Gezer; Pelin Oğuzkurt; Abdulkerim Temiz; Filiz Aka Bolat; Akgün Hiçsönmez (Elsevier, 2016)
Congenital cervical teratomas are rare and usually large enough to cause respiratory distress in the neonatal period. We present two cases of congenital huge cystic neck masses in which distinguishing cervical cystic hygroma and congenital cystic teratoma was not possible through radiologic imaging techniques. Experience with the first case, which was initially diagnosed and treated as cystic hygroma by injection sclerotherapy, led to early suspicion and surgery in the second case. The masses were excised completely and histopathologic diagnoses were congenital teratoma in both patients. Our aim is to review congenital huge neck masses causing respiratory distress in early neonatal life to highlight this dilemma briefly with these interesting cases.